2011
DOI: 10.1371/journal.pone.0022912
|View full text |Cite
|
Sign up to set email alerts
|

EEG Microstate Analysis in Drug-Naive Patients with Panic Disorder

Abstract: Patients with panic disorder (PD) have a bias to respond to normal stimuli in a fearful way. This may be due to the preactivation of fear-associated networks prior to stimulus perception. Based on EEG, we investigated the difference between patients with PD and normal controls in resting state activity using features of transiently stable brain states (microstates). EEGs from 18 drug-naive patients and 18 healthy controls were analyzed. Microstate analysis showed that one class of microstates (with a right-ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 60 publications
4
65
0
Order By: Relevance
“…In our study, fitting parameters and topography of class D were comparable between the groups and previous studies, which indicates that patients with SD do not have a distinct frontal lobe dysfunction from an electrophysiological view. In addition, Kikuchi et al (2011) showed that panic disorder patient had decreased duration and contribution of class A, which indicated a correlation of class A with anxiety. In the current study, patients with SD evinced a normal class A, both topographically and in terms of the fitting parameters.…”
Section: Discussionmentioning
confidence: 91%
“…In our study, fitting parameters and topography of class D were comparable between the groups and previous studies, which indicates that patients with SD do not have a distinct frontal lobe dysfunction from an electrophysiological view. In addition, Kikuchi et al (2011) showed that panic disorder patient had decreased duration and contribution of class A, which indicated a correlation of class A with anxiety. In the current study, patients with SD evinced a normal class A, both topographically and in terms of the fitting parameters.…”
Section: Discussionmentioning
confidence: 91%
“…Increased coverage of class A microstates was reported in individuals at high risk for psychosis (Andreou et al 2014) and in patients with panic disorder (Kikuchi et al 2011). Interestingly, the practice of TM is known to reduce anxiety (Eppley et al 1989;So and Orme-Johnson 2001).…”
Section: Clinical Comparisonsmentioning
confidence: 99%
“…Koenig et al [46] identified 4 normative microstate maps based on a sample of about 500 normal subjects. The meaning of each microstate map is still not precisely resolved, but certain classes, for example a microstate class labelled D, have been shown to be shortened in schizophrenia patients, especially during hallucinations [38,47,48,49,50,51], and the duration of another microstate class labelled A was shorter in patients suffering from panic disorder than in healthy controls [52]. Recently, some interesting studies reported a relationship of microstate maps and RSNs.…”
Section: Review Of the Currently Employed Qeeg Parametersmentioning
confidence: 99%